Impact And Strategy: Navigating Hybrid War Challenge In Pakistan (Journal of Namibian Studies : History Politics Culture, 2023)
Almost every nation or society faces a grave threat of hybrid war. Various states are mulling over the impact and countering strategy within their policy circles. This study aims to understand how a country like Pakistan navigates a hybrid war challenge. However, it is not a new reality. Different countries like Pakistan, India, America, Iran, Russia, and Israel have their perspectives on hybrid warfare. It has been evolving for centuries, but its manifestation in the modern day has increased. Taking advantage of politico-ethnic fault lines, socio-religious weaknesses, and identity conflicts, hybrid warfare promotes employing all tools available to subdue an adversary's will, including regular or irregular, conventional, or unconventional methods of combat. It is gaining popularity among international strategists. After the conflict between Russia and Ukraine, the global security community's interest increased considerably. In context, this paper attempts to understand how Pakistan navigates the hybrid war challenge. It also discusses its impact and suggests a countering strategy to deal with increasing hybrid warfare against Pakistan.